Association between Smartphone Addiction and Physical Activity, Sleeping Hours among Medical Science Students in Duhok City - Rebar Y. Abdullah; Kawther M. Galary; Robar A. Majid (Polytechnic Journal)
Background and Aim: Smartphones become a part of today’s life. In spite of the convenience, it contributes to our daily lives and activities, one of the most important problems is smartphone addiction. As known, smartphone addiction is a type of technological addiction or non-substance addiction. The present study is to investigate the association between smartphone addiction and physical activity, sleeping hours among medical science students in Duhok City. Subjects and Methods: A cross-sectional study design carried out with 295 students in medical science colleges in the Duhok City of both gender. Self-reported data collected from December 15, 2019, to January 22, 2020. Structured questionnaire has been used to gather data related to sociodemographic, physical activity, sleeping hours, and smartphone addiction. Results: The study found most students, 78.3% have smartphone addiction, 78% of medical science students are at low physical activity range, and only 2% of students are at normal physical activity range, also revealed 20% of students were inactive. According to daily sleeping hours, more than half of them, 61.7% were in a healthy range of sleeping; however, no statistically significant association found between smartphone addiction with physical activity, sleeping hours while finding a highly statistically significant association between smartphone addiction with gender. Conclusion: The current study figure out smartphone addiction prevalence was very high among medical science college students. Smartphone addiction showed an effect in increasing sedentary health behavior like low physical activity and poor sleeping quality with no statistically significant association.